STEAM EDUCATION METHODOLOGY FOR PRESCHOOL CHILDREN’S SCHOOL PREPARATION USING DIGITAL TECHNOLOGIES - Zoyirova , Nargiza Botir qizi; Boymatova, Khumora Azam qizi; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
This article contributes to STEAM education and preschool readiness by teaching preschoolers to Steam using modern learning platforms, websites, author-created websites, and computer programs. Information about computer programs designed to keep children busy and develop memory, reasoning, and logic; programs that teach children the alphabet of multiple languages; and websites and platforms that address child development. Offers. This article describes how the STEAM teaching methodology was born and what its methodological foundations are based on.